Activity‐based cost of platelet transfusions in medical and surgical inpatients at a US hospital. Issue 9 (27th March 2021) - Hofmann, Axel; Ozawa, Sherri; Shander, Aryeh
Abstract : Background and objectives: Previous studies by the Cost of Blood Consensus Conference (COBCON) have used a comprehensive, standardized and generalizable activity‐based costing (ABC) model to estimate the cost of red blood cell transfusions and plasma transfusion. The objective of this study was to determine the total cost of platelet transfusions in a real‐world US hospital inpatient setting. Materials and methods: This database analysis study retrospectively collected costs for all activities related to platelet transfusion in a single‐acute care US teaching hospital in 2017. Costs were collected in a stepwise manner using a custom ABC model which mapped the technical, administrative and clinical processes involved in the transfusion of platelets. Results: For the 15 024 inpatients included in the analysis, 6335 (42·2%) were given a blood type and screen, and 941 (6·3%) received a transfusion of one or more blood products. A total of 333 platelet units were transfused in 131 patients (mean 2·54 units per patient): 211 (63·4%) units in medical inpatients and 122 (36·6%) in surgical inpatients. The total cost was $1359·99 per platelet unit, corresponding to $3457·06 per inpatient. Acquisition costs made up the largest proportion of the total cost (45·1%) followed by direct and indirect overheads (38·7%) and hospital processes costs (16·3%). Conclusion: This is the first study to use an ABC costing model to determine the full cost of platelet transfusions within a US inpatient setting. This provides a useful reference point for comparisons with other transfusion products, and considerations for cost reduction.